Mentha pulegium Extracts Showed Strong Antimicrobial And Cytotoxic Effects in Vitro - Dalkilic, Semih; Kadiolu Dalkilic, Luetfiye; Fidan, Songuel; Timurkaan, Mustafa; Uygur, Luetfue; Akay, Goekhan; Korkmaz, Ismail (Kahramanmaras Sutcu Imam Univ Rektorlugu, 2023)
Mentha pulegium is a medicinally important and well-known plant and used for various purposes such as medicinal, nutritional and spice. We are analyzed to observe the antimicrobial, antioxidant and cytotoxic properties of M. pulegium extracts in this study. The antimicrobial activity of M. pulegium was tested using the agar well method. MIC, MBC and antimicrobial activity were tested on Staphylococcus aureus (ATCC 25923), Klebsiella pneumoniae (ATCC 700603), Escherichia coli (ATCC 25322), Bacillus megaterium (DSM32) and Candida albicans (FMC17) microorganisms. Clindamycin (2 mu g) and Amoxicillin (30 mu g) were used as positive control and Dimethylsulfoxide (DMSO) as negative control. Cytotoxic activity of extracts at different concentrations obtained from solvents such as acetone, chloroform and methanol using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) test method. Cell death patterns after exposure to different concentrations of the extracts on human breast cancer (MDA-MB-231), human pancreatic cancer (PANC1), human ovarian cancer (OVCAR3) and human lung cancer (A549) cell lines were determined accordingly. As a result, it was determined that M. pulegium extract has a strong antimicrobial activity spectrum and cytotoxic effect.
Keywords: Antimicrobial; Antioxidant; Apoptosis; Cytotoxicity; Mentha pulegium